Black rage in the American prison system - Noble, Rosevelt (Criminal justice recent scholarship, 2006)
Approaching taboo topics -- Race and prison violence -- Understanding Black rage -- Building the theoretical model -- Data summary and statistical design -- Cross-sectional models and prison violence -- Institutional changes and prison violence -- Prison violence, Black rage, and implications